Aleksandr Makedonskij v literaturnoj i Fol'klornoj tradicii - Kostûhin, Evgenij Alekseevič. (Moskva : Nauka, 1972)
Summary.
Keywords: Aleksanteri Suuri, -- Makedonian kuningas, -- 356 eKr.-323 eKr; historialliset tarinat (kansantarinat); kansanperinne; kronikaatit; kirjallisuus; historiska sägner; folktradition; kronikat; litteratur